Biphasic ROS production, p53 and BIK dictate the mode of cell death in response to DNA damage in colon cancer cells - Kutuk, Ozgur (PLoS One, 2017)
Necrosis, apoptosis and autophagic cell death are the main cell death pathways in multicellular organisms, all with distinct and overlapping cellular and biochemical features. DNA damage may trigger different types of cell death in cancer cells but the molecular events governing the mode of cell death remain elusive. Here we showed that increased BH3-only protein BIK levels promoted cisplatin- and UV-induced mitochondrial apoptosis and biphasic ROS production in HCT-116 wild-type cells. Nonetheless, early single peak of ROS formation along with lysosomal membrane permeabilization and cathepsin activation regulated cisplatin- and UV-induced necrosis in p53-null HCT-116 cells. Of note, necrotic cell death in p53-null HCT-116 cells did not depend on BIK, mitochondrial outer membrane permeabilization or caspase activation. These data demonstrate how cancer cells with different p53 background respond to DNA-damaging agents by integrating distinct cell signaling pathways dictating the mode of cell death.